2020
DOI: 10.1002/acr.23995
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Real‐Life Management Strategies in Gout: Data From Two Protocolized Gout Clinics

Abstract: Objective. To compare outcomes of 2 gout clinics that implemented different treatment strategies. Methods. Patients newly diagnosed with gout and a follow-up of 9-15 months were included. Co-primary outcomes were the proportion of patients reaching a serum uric acid (UA) ≤0.36 mmoles/liter and free of flares. Secondary outcomes were the proportion of patients requiring treatment intensification and experiencing adverse events. One clinic adopted a strict serum UA (≤0.30 mmoles/liter target) strategy, with earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Our real-life results of over 1,100 patients with a T2T strategy showed that it is feasible in about 80% to get to a more lenient 0.36 mmol/L target, comparable or somewhat less when compared with a real-life study from Norway [4], with only 2 urate lowering drugs, i.e., allopurinol and febuxostat, and the British nurse-led gout study in which 95% reached the 0.36 mmol/L target [5]. The presented results align with previous Dutch work showing that a strict urate-driven therapy using a urate-driven approach reached the biochemical sUA < 0.36 mmol/L target in about 85% of patients [6,7].…”
Section: Discussionsupporting
confidence: 80%
“…Our real-life results of over 1,100 patients with a T2T strategy showed that it is feasible in about 80% to get to a more lenient 0.36 mmol/L target, comparable or somewhat less when compared with a real-life study from Norway [4], with only 2 urate lowering drugs, i.e., allopurinol and febuxostat, and the British nurse-led gout study in which 95% reached the 0.36 mmol/L target [5]. The presented results align with previous Dutch work showing that a strict urate-driven therapy using a urate-driven approach reached the biochemical sUA < 0.36 mmol/L target in about 85% of patients [6,7].…”
Section: Discussionsupporting
confidence: 80%
“…During follow-up, an sUA value of <360µml/L was numerically more frequently reached in the more ambitious approach by 83% versus 74%, but differences were not statistically significant. 28 In a Mexican study, the target sUA was achieved in only 50%–70% after 3–4 years in spite of regular visits, 29 and response rates by 12 months among general practitioners in the UK with sUA <360 µmol/L were 45%. 30 …”
Section: Discussionmentioning
confidence: 95%
“…The response rate in a randomised controlled trial from Nottingham, UK, was even higher than in our study with 95% after both 1 and 2 years, when care was provided by a nurse combining ULT and education as compared with primary care. 20 A recent study from the Netherlands compared two treatment strategies, 28 a more ambitious approach with a target of sUA <300 mol/L as compared with a target <360 µmol/L. During follow-up, an sUA value of <360µml/L was numerically more frequently reached in the more ambitious approach by 83% versus 74%, but differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In this treat-to-target (T2T) approach, serum urate is lowered by increasing the dose or combining ULT until the target of <0.36mmol/l (6mg/dl) or even <0.30mmol/l (5mg/dl) in patients with tophi, severe polyarticular gout and/or erosions is reached [3][4][5][6] and maintained at target. Although globally rheumatologists strongly believe in a continued T2T approach [7], an alternative strategy also commonly used in daily practice is a treat-to-avoidsymptoms (T2S) approach [8]. In this T2S strategy, ULT is solely dosed on symptoms, regardless of serum urate levels.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%